2021
DOI: 10.1089/ham.2020.0059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eight Weeks Altitude Training on the Aerobic Capacity and Microcirculation Function in Trained Rowers

Abstract: Background: The mechanism of aerobic improvement after altitude training (AT) has not been resolved yet. Few studies have looked at microcirculation changes after AT in athletes. Materials and Methods: Thirty-three male rowers were recruited and divided into either the AT (n = 18, altitude 2,280 m) or the sea level training (ST group, n = 15, altitude 50 m) for 8 weeks training. Microcirculation function was monitored using a laser Doppler flowmeter. VO 2peak and ergometer 5 km time trial (Er5k) were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 48 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…Microcirculation is the main site for material exchange and metabolite discharge ( Tibirica et al, 2018 ). The microcirculation function is directly related to microcirculation capillary formation and its blood perfusion level ( Meng et al, 2021 ). Skeletal muscle is a highly metabolically active organ that accounts for about 40% of the total body mass; it possesses more microcirculation capillaries than other tissues ( Payne and Bearden, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microcirculation is the main site for material exchange and metabolite discharge ( Tibirica et al, 2018 ). The microcirculation function is directly related to microcirculation capillary formation and its blood perfusion level ( Meng et al, 2021 ). Skeletal muscle is a highly metabolically active organ that accounts for about 40% of the total body mass; it possesses more microcirculation capillaries than other tissues ( Payne and Bearden, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle is a highly metabolically active organ that accounts for about 40% of the total body mass; it possesses more microcirculation capillaries than other tissues ( Payne and Bearden, 2006 ). The skeletal muscle microcirculation is a highly dynamic system, the function of which plays an important role in disease diagnosis, as well as physiological and biomechanical monitoring of athletes ( Nyberg et al, 2015 ; Meng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 & Appendix 5 ). 6 , 44 , 45 , 46 , 47 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101
Fig. 1 PRISMA 2020 flow diagram for new systematic reviews which included searches of databases, registers and other sources.
…”
Section: Resultsmentioning
confidence: 99%
“…Regarding hematological parameters, hemoglobin parameters demonstrated a likely moderate increase after LHTH training (Bonetti and Hopkins, 2009). Few studies have shown the effects of altitude training on performance in rowers, examining peripheral effects such as cutaneous microcirculation over four to 8 weeks of training (Meng et al, 2019;Meng et al, 2021). However, the evidence regarding the effect of LHTH training on V_O 2max , lactate/ ventilatory thresholds, and exercise economy/efficiency in elite rowers is lacking.…”
Section: Introductionmentioning
confidence: 99%